Socioeconomic and Political Inequalities as Factors of Youth Militancy - Azam, Muhammad (Pakistan Languages and Humanities Review, 2024)
The objective of this study is to examine the main variables related to inequality that drive recruitment into militant organisations. The study is focused on economic and income inequality. Young people are pushed by several causes to join militant groups. Qualitative in nature, the study finds several potential causes of militancy, including variations in opportunity and gender, and discrepancies in the educational system. Disgruntled youth are drawn to militant agendas, while inequality feeds hatred and rage. One can also include variations in household income or per capita income across populations within a country or between countries as a factor for militancy. The disparity between rural and urban areas is also related to inequality of opportunity. Facilities for health, education, and other needs are either nonexistent or in disarray in rural communities. The state cannot solve this massive problem single-handedly. Society also bears a responsibility.